2019
DOI: 10.1177/1120700019860492
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of femoral head avascular necrosis following femoral neck fracture: “pin-tract sign” of 99mTc-HDP pinhole bone scan after metallic fixation

Abstract: Objective: To evaluate the predicting value of 99mTc-hydroxydiphosphonate (HDP) pinhole bone scan in development of osteonecrosis of femoral head (ONFH) in patients with femoral neck fracture after cannulated screw fixation. Methods: Pinhole bone scan of patients with metallically fixed femoral neck fracture from 2001 to 2015 were retrospectively reviewed. Initial pinhole bone scan was obtained within 2–3 weeks after surgery. Findings of initial pinhole bone scan were divided in to 4 groups. Group CU included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Preoperative quantitative indicators included a percentage of photon defect [ 41 ], head-to-head uptake ratio or head-to-acetabulum uptake ratio [ 42 ], and the ratio of radionuclide uptake of the affected fractured femoral head to the healthy contralateral femoral head (F/N) [ 43 , 44 ]. Postoperative quantitative indicators include the mean standardized uptake value of the femoral head (SUV) [ 45 , 46 ]. Park et al [ 41 ] concluded that the percentage of photon defect in the femoral head was a useful index to determine the surgical methods for FNFs, considering hip replacement when the photon defect was greater than 15%, and internal fixation if the photon defect was less than 15%.…”
Section: Resultsmentioning
confidence: 99%
“…Preoperative quantitative indicators included a percentage of photon defect [ 41 ], head-to-head uptake ratio or head-to-acetabulum uptake ratio [ 42 ], and the ratio of radionuclide uptake of the affected fractured femoral head to the healthy contralateral femoral head (F/N) [ 43 , 44 ]. Postoperative quantitative indicators include the mean standardized uptake value of the femoral head (SUV) [ 45 , 46 ]. Park et al [ 41 ] concluded that the percentage of photon defect in the femoral head was a useful index to determine the surgical methods for FNFs, considering hip replacement when the photon defect was greater than 15%, and internal fixation if the photon defect was less than 15%.…”
Section: Resultsmentioning
confidence: 99%
“…Among the fractures classified according to the Pipkin system, type III fractures (i.e., femoral neck fractures with femoral head fractures) have unfavorable clinical and radiologic outcomes [ 25 ]. Simultaneous fractures of the femoral neck and head contribute to difficulty in performing reduction and fixation, and AVN can develop owing to medial femoral circumflex artery injury that occurs with the fracture [ 26 ]. In this study, femoral neck fractures frequently caused complications with two of the three (66.7%) patients with femoral neck fractures developing AVN.…”
Section: Discussionmentioning
confidence: 99%
“…The most serious complication of femoral neck fracture is avascular necrosis of the femoral head and internal xation failure [21,22], and there are many factors leading to these complication, such as the age of the patient, general health status, combined underlying diseases, injury mechanism, fracture displacement, osteoporosis, etc., and the above factors cannot be controlled by the doctor [23,24]. What can interfere is the operation time, the quality of fracture reduction and the choice of internal xation.…”
Section: Complicationsmentioning
confidence: 99%